Amorphous-amorphous phase separation in hydrophobically-modified starch–sucrose blends II. Crystallinity and local free volume investigation using wide-angle X-ray scattering and positron annihilation lifetime spectroscopy. (July 2016) - Hughes, David; Tedeschi, Concetta; Leuenberger, Bruno; Roussenova, Mina; Coveney, Abigail; Richardson, Robert; Bönisch, Gabriela Badolato; Alam, M. Ashraf; Ubbink, Job
Abstract: Positron Annihilation Lifetime Spectroscopy (PALS) has been employed to characterize the temperature dependence of the local free volume of hydrophobically-modified starch (HMS) – sucrose (S) blends as a function of blend composition and water content. The findings from PALS support the conclusions drawn from thermodynamic characterization using Differential Scanning Calorimetry (DSC) showing evidence of limited phase separation between the HMS and S phases, inferred from the drastic change in the temperature dependence of the average size of the local free volume element as a function of blend composition. The effect of water content on the average local free volume element size is in good agreement with previous studies on simpler carbohydrate polymer/low molecular weight inclusion blends, however, the width of the free volume distribution is also observed to be affected by water content. This is interpreted to be related to the heterogeneity of the free volume holes, which is higher for phase-separated systems comprising phases of different composition and molecular weight distribution. Wide angle X-ray scattering (WAXS) was employed to study the crystallinity of the blends, showing limited crystallinity is present in the blends at the highest water contents with origin in the corn starch (CS) added during processing, and not the HMS and S phases. Graphical abstract: Highlights: Phase separation is observed in amorphous blends of OSA starch and sucrose. The phase separation could be confirmed by PALS. PALS is a sensitive method to explore the free volume of complex matrices. The PALS results allow the optimization of multi-phase encapsulation glass systems.